APORTES SOBRE LA FAMILIA DEL FARMACODEPENDIENTE - Sáenz Rojas, Mario Alberto (2023)
This article presents the importance of family in both social and psychological constitution of the personality. Another issue is the persons basically dependence on family while drugs use, and are referenced to national statistics. Besides, there’s a summary of the family’s characteristics of the drug dependent person. These characteristics were obtained from clinical research in two different models: the systemic and the psychodynamic, which more important concepts are described. The complement of the models is referenced and its contributions for know of the patients addicts behavior in therapy.